Additions to the Flora of China: seven new species of Elatostema (Urticaceae) from the karst landscapes of Guangxi and Yunnan - Wei, Y. G.; Monro, A. K.; Wang, W. T. (Phytotaxa, 2011)
Seven new species of Elatostema from southwestern China are described and illustrated. Affinities of the species are discussed and Global Species Conservation Assessments presented. The new species are: E. celingense (Critically Endangered) which most closely resembles E. backeri, E. hezhouense (Critically Endangered) which most closely resembles E. ichangense, E. lui (Vulnerable) which most closely resembles E. platyceras, Elatostema multicaule (Vulnerable) which most closely resembles E. asterocephalum, E. nianbense (Vulnerable) which most closely resembles E. filipes, E. retrorstrigulosum (Endangered) which most closely resembles E. balansae and E. yachense (Vulnerable) which most closely resembles E. xinningense. All of the new species are endemic to China.